2016
DOI: 10.1016/j.jvs.2016.01.047
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic type and risk of myocardial infarction after carotid endarterectomy in the Carotid Revascularization Endarterectomy versus Stenting Trial (CREST)

Abstract: Objectives Carotid endarterectomy (CEA) is usually performed under general anesthesia (GA) although some advocate regional anesthesia (RA) to reduce hemodynamic instability, allow neurologic monitoring and selective shunting. RA does not reduce risk of periprocedural stroke or death, although some series show a reduction in myocardial infarction (MI). We investigated the association of anesthesia type and periprocedural MI among patients receiving GA or RA for CEA and patients undergoing carotid artery stentin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 34 publications
0
39
0
Order By: Relevance
“…A recent study of the Carotid Revascularization Endarterectomy versus Stenting Trial (CREST) cohort by Hye et al showed increased periprocedural MI with GA vs RA. 9 Similarly, two studies of the National Surgical Quality Improvement Program database by Leichtle et al and Kfoury et al suggested increased cardiac morbidity after GA vs RA for CEA. 6,8 Nevertheless, a separate study of the National Surgical Quality Improvement Program database by Schechter et al showed no difference in patient outcomes.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A recent study of the Carotid Revascularization Endarterectomy versus Stenting Trial (CREST) cohort by Hye et al showed increased periprocedural MI with GA vs RA. 9 Similarly, two studies of the National Surgical Quality Improvement Program database by Leichtle et al and Kfoury et al suggested increased cardiac morbidity after GA vs RA for CEA. 6,8 Nevertheless, a separate study of the National Surgical Quality Improvement Program database by Schechter et al showed no difference in patient outcomes.…”
Section: Discussionmentioning
confidence: 95%
“…[2][3][4] The General Anesthesia versus Local Anesthesia for Carotid Surgery (GALA) trial in 2008 was recognized as a landmark study showing no difference in morbidity or mortality under local anesthesia vs GA. 5 The ideal anesthetic technique, however, has been the subject of intense study, with several studies reporting conflicting results and some suggesting a tendency toward increased cardiac morbidity with GA. [6][7][8][9] Advocates for performing CEA under RA cite reduction in hemodynamic instability and indisputably reliable neurologic monitoring, but many still prefer to employ GA as benefits of RA have not been clearly demonstrated, reliable RA may not be available in all centers, and a certain amount of movement by the patient during the procedure may not be uniformly tolerated.…”
mentioning
confidence: 99%
“…A priori, the authors expected a significant benefit of regional anesthesia in TCAR, a minimally invasive procedure, because several studies have shown a decrease in morbidity and mortality in patients after CEA, a more invasive procedure with a greater risk of myocardial ischemia. 15 Although there was no mortality difference, Urman et al showed lower rates of perioperative blood loss and pulmonary complications among the regional anesthesia cohort after CEA. 3 Other studies in CEA cohorts have shown a mortality benefit in the regional anesthesia group.…”
Section: Discussionmentioning
confidence: 97%
“…14 However, recent studies have shown regional anesthesia to be associated with lower morbidity and mortality. [15][16][17] As such, the choice of anesthesia type for carotid artery revascularization continues to be under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, due to general anaesthesia, periprocedural risk with CEA might be higher as compared to CAS. In comparison, regional anaesthesia was found to be associated with lower rates of in-hospital strokes or death [36] as well as periprocedural myocardial infarction [37] and therefore could be considered an alternative. However, with CEA, diastolic hypertension has proven to be an independent risk factor of stroke.…”
Section: Agementioning
confidence: 99%